Josef Pieper on the spiritual life : creation, contemplation, and human flourishing - Warne, Nathaniel A. (University of Notre Dame Press, 2023)
Warne's original study provides an insightful analysis of the role of contemplation and creation in the thought of Josef Pieper, illustrating the importance of this practice to earthly happiness and human flourishing. What is the relationship between creation, contemplation, human flourishing, and moral development? Nathaniel Warne's Josef Pieper on the Spiritual Life offers a sophisticated answer to this question through a systematic analysis of philosopher Josef Pieper's (1904-1997) thought. Warne's examination centers on the role of contemplation and creation in Pieper's thinking, arguing that contemplation of the created order is a key feature of earthly happiness. By emphasizing the importance of contemplation, Pieper illustrates the deep interconnections between ethics, creation, and spirituality. For Warne, to posit a binary between the contemplative life and active life creates a false dichotomy. Following Pieper, Warne claims that theology and spirituality cannot be bracketed from ethics and social action--indeed, our lived experience in the world blurs the lines between these practices. Contemplation and action are closer together than are typically assumed, and they have important implications for both our spiritual development and our engagement with the world around us. Ultimately, Warne's emphasis on creation and contemplation represents an attempt to resist a view of ethics and the spiritual life that is divorced from our environment. In response to this view, Warne argues that we need a renewed sense that creation and place are important for self-understanding. Contemplation of creation is, fundamentally, a form of communion with God--we thus need a more robust sense of how ethics and politics are rooted in God's creative action. Taking Pieper as a guide, Warne's study helps to deepen our thinking about these connections.
Keywords: Pieper, Josef, -- 1904-1997.; Pieper, Josef, -- 1904-1997; Philosophical theology.; Contemplation.; Happiness.; Théologie philosophique.; Bonheur.; PHILOSOPHY / Religious; Philosophical theology; Contemplation; Happiness; Electronic books.